Implementation of the Hadith about Deliberation: A Case Study of Catfish Farming as A Consensus Space for Farmers: Implementasi Hadis tentang Musyawarah: Studi Kasus Budidaya Ikan Lele sebagai Ruang Musyawarah bagi Petani - Ahmad Imron Rozuli; Dodyk Pranowo; Rahmi Nurdiani; Muhammad Akhid Syib’li; Purba, Dano; Ryan Renwarin; Adhinugraha Wirayudha (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2024)
Conflicts among farmers over water resource management are often a significant problem, especially during the dry season. This is made all the more complex by the fact that these problems occur on a protracted basis without any concrete action being taken to resolve them. One of these realities occurs in the community of Kedungrejo Village, Malang District. The emergence of catfish cultivation is an alternative business and an effort to form a space for community consensus in discussion. This study analyzes the role of catfish farming as a consensus space in two forms of questions. First, how is the relevance between the hadith about deliberation and catfish cultivation as a community consensus space? Second, how is the impact of catfish farming as a consensus space in breaking the tension in the community? Using a descriptive qualitative approach and Miles and Huberman's analysis, this study found that catfish farming is not only an alternative economic solution but also fosters social solidarity through deliberation. Meanwhile, the hadith about deliberation in farmers' socio-economic practices confirms that Islamic values can be applied in community life. As a result, catfish cultivation in Kedungrejo is proof that deliberation can be a tool for conflict resolution while improving community welfare.